LncKdm2b controls self‐renewal of embryonic stem cells via activating expression of transcription factor Zbtb3. (13th March 2018) - Ye, Buqing; Liu, Benyu; Yang, Liuliu; Zhu, Xiaoxiao; Zhang, Dongdong; Wu, Wei; Zhu, Pingping; Wang, Yanying; Wang, Shuo; Xia, Pengyan; Du, Ying; Meng, Shu; et al.
Abstract: Divergent long noncoding RNAs (lncRNAs) represent a major lncRNA biotype in mouse and human genomes. The biological and molecular functions of the divergent lncRNAs remain largely unknown. Here, we show that lncKdm2b, a divergent lncRNA for Kdm2b gene, is conserved among five mammalian species and highly expressed in embryonic stem cells (ESCs) and early embryos. LncKdm2b knockout impairs ESC self‐renewal and causes early embryonic lethality. LncKdm2b can activate Zbtb3 by promoting the assembly and ATPase activity of Snf2‐related CREBBP activator protein (SRCAP) complex in trans . Zbtb3 potentiates the ESC self‐renewal in a Nanog‐dependent manner. Finally, Zbtb3 deficiency impairs the ESC self‐renewal and early embryonic development. Therefore, our findings reveal that lncRNAs may represent an additional layer of the regulation of ESC self‐renewal and early embryogenesis. Synopsis: The long noncoding RNA lncKdm2b promotes activity of the chromatin remodeling complex SRCAP, thereby promoting Zbtb3 expression and Nanog‐dependent embryonic stem cell (ESC) renewal and embryonic development. LncKdm2b is highly expressed in ESCs and early embryoes. LncKdm2b deletion impairs ESC self‐renewal and early embryonic development. LncKdm2b activates Zbtb3 by promoting the ATPase activity of SRCAP subunit. Zbtb3 potentiates the ESC self‐renewal in a Nanog‐dependent manner. Zbtb3 deficiency disrupts ESC self‐renewal and early embryonic development. Abstract : The long noncoding RNA lncKdm2b promotes activity of the chromatin remodeling complex SRCAP, thereby promoting Zbtb3 expression and Nanog‐dependent embryonic stem cell (ESC) renewal and embryonic development.